A Project Report on Intrusion Detection in Homogeneous and Hetrogeneous Wireless Sensor Network - ABHISHEK KUMAR, JAMAL AMIR, ANUP AGARWAL and ATONU NAYAK (2009)
INTERNAL GUIDE: SWATHI PRIYA, MVJCE EXTERNAL GUIDE: SUPRIYA, TECHNICAL TRAINER HCL INFOSYSTEM PVT
Keywords: Intrusion Detection in Homogeneous and Hetrogeneous Wireless Sensor Network